2019
DOI: 10.1098/rspb.2019.2614
|View full text |Cite
|
Sign up to set email alerts
|

Vector-borne parasite invasion in communities across space and time

Abstract: While vector-borne parasite transmission often operates via generalist-feeding vectors facilitating cross-species transmission in host communities, theory describing the relationship between host species diversity and parasite invasion in these systems is underdeveloped. Host community composition and abundance vary across space and time, generating opportunities for parasite invasion. To explore how host community variation can modify parasite invasion potential, we develop a model for vector-borne parasite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It has been shown that changes in biodiversity can either amplify or dilute pathogen transmission, through multiple mechanisms which can sometimes occur within the same system (Clay et al, 2009a; 2009b; Faust et al, 2017; Huang et al, 2015; Luis et al, 2018; Miller & Huppert, 2013; Ogden & Tsao, 2009; Roche & Guégan, 2011; Rohr et al, 2015; Swei et al, 2011; Wood et al, 2020). In the case of vector‐borne diseases, it has been stressed that the ecology and feeding habits of arthropod vectors must also be considered (Carlson et al, 2009; Hamer et al, 2011; Laporta et al, 2013; Loss et al, 2009; McGregor et al, 2018; Miller & Huppert, 2013; Ogden & Tsao, 2009; Park et al, 2016; Randolph & Dobson, 2012; Roche & Guégan, 2011; Roche et al, 2013; Swei et al, 2011; Titcomb et al, 2017; Vinson & Park, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that changes in biodiversity can either amplify or dilute pathogen transmission, through multiple mechanisms which can sometimes occur within the same system (Clay et al, 2009a; 2009b; Faust et al, 2017; Huang et al, 2015; Luis et al, 2018; Miller & Huppert, 2013; Ogden & Tsao, 2009; Roche & Guégan, 2011; Rohr et al, 2015; Swei et al, 2011; Wood et al, 2020). In the case of vector‐borne diseases, it has been stressed that the ecology and feeding habits of arthropod vectors must also be considered (Carlson et al, 2009; Hamer et al, 2011; Laporta et al, 2013; Loss et al, 2009; McGregor et al, 2018; Miller & Huppert, 2013; Ogden & Tsao, 2009; Park et al, 2016; Randolph & Dobson, 2012; Roche & Guégan, 2011; Roche et al, 2013; Swei et al, 2011; Titcomb et al, 2017; Vinson & Park, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The breadth of the host’s diet is further positively correlated to their accumulation of microparasites due to diverse exposure [ 68 ]. Similarly, vectors of zoonotic disease tend to feed on multiple host species, allowing populations to adapt to varying host availability [ 69 ]. For a vector-borne pathogen to cause zoonotic concern, it’s vector typically would preferentially feed on humans [ 70 ].…”
Section: From Animals and Pathogens: What Drives The Zoonotic Potential?mentioning
confidence: 99%
“…Then we relaxed this condition by assuming that there was no relationship between R 0i and species abundance (neutral). Finally, we considered a negative relationship between R 0i and host abundance, where the most abundant species were the least competent (Vinson and Park, 2019).…”
Section: Epidemiological Traitsmentioning
confidence: 99%